Theoretical problems of component-based structural synthesis - Vaidas Giedrimas; Audronė Lupeikienė (Lietuvos Matematikos Rinkinys)
The Structural Synthesis of Programs (SSP) method is based on the idea that programs can be constructed taking into account only their structural properties. This method has been successfully used to synthesise structural and object-oriented programs. This paper presents the research on the SSP in the component based environment. It discuses the possibility of SSP method application to software synthesis from components and shows the main problems: problem of the specification, problem of reusable components and problem of undefined components. The possible solutions to those problems are provided too.